New Insights on the Regulation of Glucosinolate Biosynthesis via COP1 and DELLA Proteins in Arabidopsis Thaliana - Frerigmann, Henning; Hoecker, Ute; Gigolashvili, Tamara (Frontiers in Plant Science, 2021)
The biosynthesis of defensive secondary metabolites such as glucosinolates (GSL) is a costly process, which requires nutrients, ATP and reduction equivalents and therefore, needs a well-orchestrated machinery while coordinating defense and growth. We discovered that the key repressor of light signaling, the CONSTITUTIVE PHOTOMORPHOGENIC 1/SUPPRESSOR OF PHYTOCHROME A-105 (COP1/SPA) complex, is a crucial component of GSL biosynthesis regulation. Various mutants in this COP1/SPA complex exhibited a strongly reduced level of GSL and a low expression of jasmonate-dependent genes. Furthermore, cop1, which is known to accumulate DELLA proteins in the dark, shows reduced gibberellin and jasmonate signaling thereby phenocopying other DELLA-accumulating mutants. This phenotype can be complemented by a dominant gain-of-function allele of MYC3 and by crossing with mutant having low DELLA protein levels. Hence, whereas SPA1 interacts with DELLA proteins in a yeast two-hybrid screen, high levels of DELLA inhibit MYC function and suppress jasmonate signaling. DELLA accumulation leads to a reduced synthesis of GSL and inhibited growth. Thus, the COP1/SPA-mediated degradation of DELLA does not only affect growth but it also regulates biosynthesis of GSLs.